Peran Muhammadiyah Dalam Pengembangan Pendidikan Islam Di Masyarakat - Khasanah, Latif Nur, Drs.Najmudn Zuhdi, M.Ag (2016)
This study aims at finding information about the role of the branch of Muhammadiyah Tegalombo, Kalijambe, Sragen in developing Islamic education in society and investigating the supporting factors and obstacles. The problems in this study is the development of the community in Tegalombo village which is not optimum. This study is a field research because more than a half of the data needed are obtained in the field. The methods used for data collection in this study are interview, observation, and documentation. The data, then, are analyzed by descriptive qualitative method. The results show that the role of the branch of Muhammadiyah Tegalombo, Kalijambe, Sragen in the field of education are providing Muhammadiyah MI (Elementary School) at Tegalombo for formal education and providing TPA (Quranic Reciting) for informal education. Besides in the field of education, there are other roles of Muhammadiyah, such as in the field religious by initiating weekly Islamic study, in the social field by creating cooperative society, and in the health field by organizing free health checking for community. Keywords: The branch of Muhammadiyah, Islamic education, Tegalombo village